The beloved community: how faith shapes social justice, from the civil rights movement to today - Marsh, Charles (Basic Books, 2005)
From church budgets to beloved community: King in Montgomery -- In the fields of the Lord: the God Movement in South Georgia -- A theology for radicals: the rise and fall of SNCC -- The burdens of perpetual freedom: the dream as hallucination -- Between the times -- Unfinished business: John Perkins and the radical roots of faith-based community building -- Building beloved communities: dispatches from the quiet revolution -- The contours of an activist faith for the twenty-first century.